Use of Lortenza for the Treatment of Arterial Hypertension - Matyakubovna, Nuralieva Rano (American Journal of Bioscience and Clinical Integrity, 2025)
22 patients aged 50 to 67 years with arterial hypertension were examined. The patients received complex therapy, including the use of antihypertensive drugs. It was found that the positive dynamics of disease manifestations occurred somewhat faster in patients who were prescribed lortensa than in patients who received antihypertensive drugs of various groups. These data allow us to conclude that the use of the drug Lortenza in patients with arterial hypertension is advisable.